2016
DOI: 10.1111/tpj.13266
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the U, M, S and C genomes of wild relatives of bread wheat (Aegilops spp.) into chromosomes and exploring their synteny with wheat

Abstract: SIGNIFICANCE STATEMENT (74WORDS)Bivariate flow cytometric analysis of DNA content and FITC-labelled microsatellites enabled all the chromosomes in the U, M, S and C genomes ofAegilopsto be discriminated and purified. Mapping COS markers with known position in the wheat genome to flow-sorted Aegilops chromosomes revealed significant evolutionary rearrangements in the U and C genomes, but not in the M and S genomes. COS markers assigned to Aegilops chromosomes will facilitate alien introgression breeding in whea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
86
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(92 citation statements)
references
References 81 publications
5
86
1
Order By: Relevance
“…The results obtained on diploid wheatgrass species agreed well with previous studies and confirmed the high transferability of COS markers between species in the Triticeae [27,39,40,63,64]. The fact that 31–50% of the amplicons obtained on perennial wheatgrass species belonging to the tertiary gene pool were polymorphic relative to those obtained in hexaploid wheat suggested that a significant part of the genetic diversity in these wild species is due to the variability of intron regions [65].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results obtained on diploid wheatgrass species agreed well with previous studies and confirmed the high transferability of COS markers between species in the Triticeae [27,39,40,63,64]. The fact that 31–50% of the amplicons obtained on perennial wheatgrass species belonging to the tertiary gene pool were polymorphic relative to those obtained in hexaploid wheat suggested that a significant part of the genetic diversity in these wild species is due to the variability of intron regions [65].…”
Section: Discussionsupporting
confidence: 90%
“…The fact that 31–50% of the amplicons obtained on perennial wheatgrass species belonging to the tertiary gene pool were polymorphic relative to those obtained in hexaploid wheat suggested that a significant part of the genetic diversity in these wild species is due to the variability of intron regions [65]. Interestingly, using the same set of COS markers a similar ratio of polymorphic loci (46–53%) was obtained in diploid Aegilops species with the U, M, S or C genomes, which are more closely related to wheat [64]. …”
Section: Discussionmentioning
confidence: 96%
“…Although the effect of technical factors cannot be ruled out, especially for weakly distorted markers that were randomly distributed across the genome, clusters of significantly distorted markers in the previously reported distorted regions for many grass species are most likely caused by genetic factors. Chromosome 1U, with the most severe segregation distortion, is homeologous to wheat group 1 chromosomes (Zhang et al 1998; Molnar et al 2016) and barley chromosome 1H (Edae et al 2016). Segregation distortion regions have been reported on the short arms of wheat group 1 chromosome (Li et al 2015), Ae.…”
Section: Resultsmentioning
confidence: 99%
“…The use of alien segments that carry novel genes depends on the extent of chromosome collinearity and meiotic pairing of alien chromosomes with homeologous chromosomes (Devos et al 1993; Lukaszewski et al 2004; Devos et al 2007; Molnar et al 2016). In the current study, the level of collinearity of Ae.…”
Section: Resultsmentioning
confidence: 99%
“…caudata has a highly asymmetric karyotype distinct from the metacentric and submetacentric chromosomes of most Triticeae species suggesting the distortion of chromosome collinearity compared to wheat. Fluorescence in situ hybridisation (FISH) and molecular marker analysis of flow-sorted C-genome chromosomes confirmed genome rearrangements (Molnár et al, 2016; Molnár et al, 2015). A set of wheat (cv.…”
Section: Introductionmentioning
confidence: 96%